2018
DOI: 10.1007/s13361-018-2003-1
|View full text |Cite
|
Sign up to set email alerts
|

Screening and Identification of the Metabolites of Water Extracts of Raw and Honey-Processed Astragalus in Rat Urine Based on UHPLC/ESI-Q-TOF-MS and Multivariate Statistical Analysis

Abstract: Radix Astragali is a famous traditional Chinese medicine and honey-processed Astragalus is a product of Radix Astragali acquired by honey-processing. These two products are widely utilized to treat various diseases. In this study, we screened bioactive components and metabolites of raw and honey-processed Astragalus in rat urine by ultra-performance liquid chromatography equipped with electrospray ionization/quadrupole time-of-flight mass spectrometry (UHPLC/ESI-Q-TOF-MS) combined with multivariate statistical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…It was assumed that these two new ingredients might have been quickly transformed in vivo and existed in the form of their metabolites. This phenomenon was in accordance with our previous study in which astragaloside II was completely hydrolyzed into astragaloside IV in rat urine [9].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…It was assumed that these two new ingredients might have been quickly transformed in vivo and existed in the form of their metabolites. This phenomenon was in accordance with our previous study in which astragaloside II was completely hydrolyzed into astragaloside IV in rat urine [9].…”
Section: Resultssupporting
confidence: 93%
“…Studies have shown that the components successfully assimilated into blood could transform the potential bioactive ingredients [8]. Seven parent compounds and 55 metabolites were explored, and 11 metabolites were first characterized in rat urine in our previous study [9]. This paper aims to explore the serum pharmacochemistry of raw and honey‐processed Astragalus and further provides the experimental basis to find the bioactive ingredients of Astragalus .…”
Section: Introductionmentioning
confidence: 99%
“…The organic layer was vacuum dried. Residues were reconstituted in 25 μL of methanol, vortexed for 1 min, ultrasonically extracted for 2 min and centrifuged at 12,000 g and 4°C for 10 min (Huang, Chen et al, ). The supernatant was used for UPLC–Q‐TOF–MS analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The secondary metabolites of Astragali Radix were analysed by UPLC‐Q‐TOF‐MS in both positive and negative ion modes (Figure 3). A total of 31 compounds were identified or putatively characterised by comparison with standard compounds, accurate mass, and databases from the literature 8,25–30 . The identified compounds were numbered according to their elution order (Table S3).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 31 compounds were identified or putatively characterised by comparison with standard compounds, accurate mass, and databases from the literature. 8,[25][26][27][28][29][30] The identified compounds were numbered according to their elution order (Table S3).…”
Section: Colour Parametersmentioning
confidence: 99%